Lid-Driven Cavity For Mantle Convection Modelling Using Lattice Boltzmann Method - umar Fauzi (Indonesian Journal of Physics, 2021)
The Lattice Boltzmann Method is one of the computational fluid dynamics methods that can be applied to simulate fluid based on the microscopic and kinetic theory of gases. In this study, earth mantle convection is simulated by combining the concept of lid-driven cavity simulation and natural convection using the Lattice Boltzmann method in a two-dimensional system (D2Q9). The results of the lid-driven cavity and natural convection simulation are comparable to previous works. This study shows that at a certain lid velocity, the direction of the moving plume is changed. This earth mantle convection simulation will give better and more reliable results by considering more complicated boundary conditions and adequate simulation systems.